PEMBATASAN WAKTU BERTAHAP UNTUK MENINGKATKAN TIME-ON-TASK DAN EFISIENSI PENYELESAIAN TUGAS MENULIS SISWA SEKOLAH DASAR - A. Anisyah Imaniah Arifuddin; Aivi, Nur; Nurhaedah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of gradually tightened time constraints on improving time-on-task and writing task completion efficiency among elementary school students. The study was motivated by findings during Guided Field Teaching Practice indicating that students required an average of 15 minutes to copy three sentences per slide, a delay linked to students' tendency to converse with peers before writing. This Classroom Action Research followed the Kemmis, McTaggart, and Nixon model across two cycles (two meetings each), with 34 fourth-grade (IV B) students as subjects. The intervention applied gradually tightened per-slide time targets (10, 7, 5, and 2 minutes) alongside an increase in the number of slides and sentences per slide at each meeting. Data were collected through records of task completion time and observation of students' writing quality. Results show total completion time decreased from 60 to 14 minutes while the writing workload increased from 12 to 28 sentences, without a meaningful decline in writing quality. These findings indicate that gradually tightened time constraints effectively improve time-on-task and writing efficiency among elementary school students.